Social Adaptation of Afghan Refugees in Malaysia - Zarkesh, N.; Baranovich, D.; Shoup, R.C. (American Scientific Publishers, 2017)
Despite the fact that Malaysia has an open policy of not recognizing refugees the country is becoming a popular hub for refugees across Asia, the Middle East and even parts of Europe who come in hopes of finding opportunities to immigrate to Western countries. However, because Malaysia does not recognize refugees, they have no legal status in the country. It is hypothesized that since refugees have no legal status, they will have a low level of social adaptation. In order to address this concern and find out the social adaptation situation of Afghan refugees living in Malaysia a qualitative analysis was conducted with Afghan refugees living in Kuala Lumpur, Malaysia. A total of 14 refugees were interviewed for this research who participated by answering a series of questions aimed at determining how they are adapting to their new environment. Responses from refugees indicate three major themes that affect how they are adapting in Malaysia. The three themes that emerged from the analysis are: doubts about safety and security, lack of support, and emotional stress. The overall conclusion drawn from this research is that the Afghan refugees residing in Malaysia have a low level of social adaptation.